Players` technical and physical performance profiles and game-to-game variation in NBA - Zhang, S.; Lorenzo, A.; Gómez, M.-A.; Liu, H.; Gonçalves, B.; Sampaio, J. (International Journal of Performance Analysis in Sport, 2017)
The aim of this study was to (i) identify technical and physical performances of basketballers according to playing position in strong and weak teams, and (ii) describe variability in game-to-game performance according to game outcome, location, quality of teams and opposition. Performance-related variables of all the 699 matches of regular season 2015-2016 in the National Basketball Association were analysed. All the comparisons were performed using magnitude-based inferences. As could be expected, results showed that technical and physical performances differed between players of strong and weak teams. In technical aspect, forwards and centres from strong teams made more three-point field goals, but fewer two-point field goals, than their counterparts from weak teams. Interestingly, forwards and guards from strong teams covered shorter distances and lower speeds than their peers from weak teams. In addition, the three-point field goals made and attempted presented high variability. Game location generally had no significant impact on the variability of players` performance. Guards exhibited relatively lower variability in technical and physical variables in comparison with players from other positions. Exploring the difference and variability of technical and physical performances of basketballers allows fine-tuning of practice and game plans in order to build up optimal winning strategies.